Pengaruh model pembelajaran kontekstual terhadap kemampuan membaca permulaan pada anak usia 5-6 tahun - Zannah, Raudatul; Satriana, Malpaleni; Rozie, Fachrul (Jurnal Warna : Pendidikan dan Pembelajaran Anak Usia Dini, 2024)
This research was motivated by the low initial reading skills of students in class B at Tiara Pertiwi Loa Janan Kindergarten, a problem was found, namely that more than half of the students in the class did not know the letters of the alphabet, factors that caused students' low initial reading skills, including inadequate learning models and media. effective. The aim of this research is to determine the influence of the contextual learning model on the beginning reading abilities of children aged 5-6 years at Tiara Pertiwi Loa Janan Kindergarten. This type of research is quantitative, namely using experimental research methods with the research type Quasi Experimental Design and the research design is Nonequivalent Control Group Design. The population in this study were all class B students at Tiara Pertiwi Loa Janan Kindergarten. The samples in this research were class B2 as the experimental class and class B4 as the control class. The initial reading ability data obtained were analyzed using descriptive statistics and inferential statistics in the SPSS 28.0 For Windows program. The results show that the posttest completeness percentage values ​​for the experimental class and control class are 100% and 20% respectively. The results of hypothesis testing using the Independent Sample T-test in the SPSS 28.0 For Windows program showed that Two-Sided p was 0.003, smaller than 0.05, thus H0 was rejected and H1 was accepted. The conclusion from the research results after treatment is that the contextual learning model has a significant effect on the beginning reading abilities of children aged 5-6 years at Tiara Pertiwi Loa Janan Kindergarten.  Using a contextual learning model with picture media and letter cards makes learning fun and more enthusiastic about recognizing letters.